Environmental analysis of crop rotations through the application of the Cereal Unit approach. (February 2021) - Volanti, M.; Savarino, F.O.; Passarini, F.; Vassura, I.; Grosso, S.A.
Graphical abstract: Highlights: Agricultural LCA to support the achievement of UN Sustainable Development Goals. Environmental comparison of two crop rotations in terms of CED and ReCiPe methods. Use of the Cereal Unit production as functional unit to compare different crops. Land use as a key indicator in assessing the life-cycle impacts of the crops. Abstract: The sustainability of agricultural practices is a key element for an effective implementation of the UN's Sustainable Development Goals, particularly relating to ending poverty and hunger, responding to climate change and supporting the natural resources. As part of ongoing research and improvement in this field, this study aims to apply Life Cycle Assessment methodology to the agricultural sector, and to discuss and support the use of Cereal Unit (CU) parameter. To overcome the differences that emerge when two or more different crops are compared, the CU can be used as a functional unit (FU) to capture all the functions of the products. This approach avoids the use of economic parameters, providing for more stable comparisons over time, as the price of agricultural products is strongly influenced by market and currency fluctuations. The robustness of this approach was tested by the assessment and comparison of the environmental burdens of two different crop rotations using a CU-based FU. The same systems were also evaluated with a revenue-based FU to assess the pros and cons of the two type of approach. The study considered Argentina, due to the high importance of its agricultural products, which are widely exported in the world. The first crop rotation, called San Justo (SJ), is the one conventionally followed in the region and provides for a low-intensity cultivation, while the other, Evergreen (EG), is the alternative which requires a more intensive exploitation of the soil. The results showed that CU approach allows reliable and stable comparisons and, in this specific case, that the conventional system has a higher environmental load, with land use being the key factor in the assessment.